Red-mud-based three-dimensional anti-crack injection type composite pavement mixture and preparation method thereof
By using red mud-based three-dimensional crack-resistant mixture in the poured composite pavement, the crack resistance of grouting and asphalt mixture is enhanced and the interface performance is improved, the problem of insufficient crack resistance of low-temperature crack resistance of the poured composite pavement is solved, and the cost-effective and efficient road crack resistance improvement is achieved.
Patent Information
- Application Number
- CN202411762411.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-25
AI Technical Summary
The existing poured composite pavement is prone to cracks at low temperatures, and the low-temperature crack resistance is poor. The existing technology research has poor economic efficiency to improve this problem and is difficult to promote on a large scale.
The red mud-based three-dimensional crack-resistant composite pavement mixture is used to enhance the crack resistance of the grouting material, and the fiber crack resistance in the open-grade asphalt mixture is used, and the interface performance improvement is used to achieve multi-dimensional crack resistance optimization.
It significantly improves the crack resistance of the pavement under low temperature conditions, reduces material procurement and transportation costs, reduces the demand for traditional building materials, and helps protect natural resources and reduces carbon emissions.
Smart Images

Figure CN119683906A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the research field of solid waste resource utilization and new technical materials for civil engineering, and specifically is a red mud-based three-dimensional crack-resistant pourable composite pavement mixture and a preparation method thereof. Background Art
[0002] According to the data from the "Statistical Bulletin on the Development of the Transportation Industry in 2023", the total mileage of my country's highways has reached 5.4368 million kilometers, ranking first in the world for 13 consecutive years. With the increase in highway mileage, maintenance tasks are becoming increasingly heavy. For asphalt concrete pavements, the main types of diseases are cracks, rutting, subsidence, looseness, etc. For cement concrete pavements, the main types of diseases are cracks, broken plates, misalignment, joint fragmentation, etc. At present, rutting and cracks have become the main disease problems of highway pavements in my country. For solving the rutting problem, the poured composite pavement has unique advantages. Its dynamic stability can reach 8 to 10 times that of ordinary asphalt pavement, and its anti-rutting performance is excellent. The poured composite pavement is to fill cement mortar in the large-void asphalt mixture to form a composite pavement structure that has the performance of both cement concrete pavement and asphalt pavement, combining the advantages of cement concrete pavement and asphalt pavement. The strength of the poured composite pavement is mainly composed of the interlocking effect of the base asphalt mixture skeleton and the strength of the grouting material after hardening. As a structural layer, it has a strong load resistance, and its modulus is between asphalt concrete and cement concrete, with the characteristics of "hardness and flexibility". On the other hand, the elastic modulus of the large-void base asphalt mixture of the poured composite pavement increases at low temperatures, and its flexibility deteriorates. It is difficult to withstand the shrinkage tensile stress caused by the temperature drop, and cracks are easily generated, and the low-temperature crack resistance is poor.
[0003] At present, the research on improving the low-temperature crack resistance of poured composite pavement is mainly carried out from the aspects of material optimization, structural design optimization and construction process improvement. For example, base asphalt with better low-temperature toughness, special modified asphalt or polymer materials with lower modulus and better elasticity are selected, grouting materials with better low-temperature performance are used, and crack-resistant fibers are added to improve their flexibility and deformation capacity at low temperatures, and reduce cracks caused by low-temperature shrinkage; for example, the thickness and combination of the structural layer of the poured composite pavement are reasonably designed, the thickness and strength of the base layer are increased, and a stress absorption layer is set, so that the pavement structure can better withstand the effects of vehicle loads and environmental factors, which can effectively reduce the occurrence of cracks. However, the current understanding of the connection between the microstructure changes of the material interface and the formation of cracks, the initiation and expansion mechanism of microcracks, and the law of crack development under the coupling of multiple factors is not clear, and further research is needed. The solution of strengthening crack resistance alone has limited effect on solving the problem of road cracks. Therefore, it is necessary to consider combining multiple solutions in different dimensions to improve the crack resistance of poured composite pavement.
[0004] Existing technical research has limited effect on improving the low-temperature crack resistance of poured composite pavement, and the economic efficiency is poor, making it difficult to promote and apply on a large scale. Therefore, exploring a new type of poured composite pavement mixture material, by enhancing the crack resistance of the grouting material itself, giving full play to the crack resistance of the fiber in the open-graded asphalt mixture, and focusing on improving the relevant interface properties to further improve the crack resistance effect, achieving the improvement of crack resistance in three dimensions, and achieving the goal of efficient resource utilization of acidic aggregates and red mud solid waste, is of great significance to the development of road materials and environmental protection in my country. Summary of the invention
[0005] Based on the problems existing in the prior art, the present invention proposes a red mud-based three-dimensional anti-cracking poured-in composite pavement mixture and a preparation method thereof. The core idea is to solve the problem of crack disease by enhancing the self-cracking resistance of the grouting material, the fiber cracking resistance of the open-graded asphalt mixture, and the cracking resistance improvement after the improvement of the interface performance, so as to achieve multi-dimensional optimization of crack resistance performance, and at the same time achieve the purpose of efficient utilization of acidic aggregates and red mud solid waste resources, which is in line with the current technological development trend.
[0006] The present invention adopts the following technical solution:
[0007] A red mud-based three-dimensional anti-cracking poured-in composite pavement mixture comprises the following components in parts by mass:
[0008] Red mud-based anti-cracking grouting material: 20-35 parts;
[0009] Red mud modified open-graded anti-cracking asphalt mixture: 65-80 parts.
[0010] Furthermore, the red mud-based anti-cracking grouting material comprises the following components in parts by mass:
[0011] 9-15 parts of untreated red mud;
[0012] 3-4 parts of calcium powder;
[0013] 1-3 parts of stimulant;
[0014] 1-3 parts of water reducing component;
[0015] Fiber 2-3 servings;
[0016] The added water and the fiber have the same mass fraction.
[0017] Furthermore, in the red mud-based anti-cracking grouting material, the fineness of the untreated red mud satisfies the 0.075mm pass rate greater than 90%, and the water content is greater than 25wt%; the calcium carbonate content of the calcium powder is greater than 95wt%, the fineness is 400 mesh and above, and the water content is less than 0.5wt%.
[0018] Furthermore, in the red mud-based anti-cracking grouting material, the activator is one of water glass and caustic soda; the water-reducing component is one of naphthalenesulfonate formaldehyde condensate and aliphatic hydroxysulfonate condensate; and the added water is ordinary tap water.
[0019] Furthermore, in the red mud-based anti-cracking grouting material, the fiber is at least one of basalt fiber, polyethylene fiber and polypropylene fiber, the fiber length ranges between 12mm-20mm, and the fineness is less than 15tex.
[0020] Furthermore, the red mud modified open-graded anti-cracking asphalt mixture comprises the following components in parts by mass:
[0021] 15-20 parts of mineral powder grade red mud;
[0022] 45-50 parts of open-graded acid aggregate;
[0023] SBS modified asphalt 3-6 parts;
[0024] Fiber 2-4 servings.
[0025] Furthermore, in the red mud modified open-graded anti-cracking asphalt mixture, the coarse aggregate material of the open-graded acidic aggregate is granite, diorite or tuff, the key sieve hole 4.75mm pass rate is 12%-18%, and the target connected porosity is 22%-28%.
[0026] Furthermore, in the red mud modified open-graded anti-cracking asphalt mixture, the particle size of the mineral powder grade red mud is less than 0.075mm, and the pH value is 7-9, which is used to adjust the pH value of the open-graded acidic aggregate, perform interface modification on the open-graded acidic aggregate, and enhance the bonding force between the interfaces.
[0027] Furthermore, in the red mud modified open-graded anti-cracking asphalt mixture, the fiber is at least one of basalt fiber, polyethylene fiber and polypropylene fiber, the fiber length ranges between 12mm-20mm, and the fineness is less than 15tex.
[0028] The present invention also provides a method for preparing the red mud-based three-dimensional anti-cracking poured-in composite pavement mixture, comprising the following steps:
[0029] S1. Firstly, the fineness and water content of the untreated red mud are detected;
[0030] S2. The fiber and the added water were placed in a container of an ultrasonic disperser and ultrasonically dispersed at a frequency of 40-60kHZ for 5-10min to prepare a uniformly dispersed fiber solution;
[0031] S3. The untreated red mud and fiber solution were placed in a mixer and slowly mixed for 2-3 min, then calcium powder, activator and water-reducing component were added in proportion, and rapidly stirred for 3-5 min to form red mud-based anti-cracking grouting material;
[0032] S4. Design the gradation of open-graded acidic aggregates, with a target connected porosity of 22%-28%, and add mineral powder-grade red mud in proportion to fill the aggregate voids to improve overall strength and stability;
[0033] S5. The mixed aggregate of the open-graded acidic aggregate and the mineral powder-grade red mud is conveyed into a heating drum through a belt, activated at a high temperature of 700°C-900°C for 3-5 minutes, and then subjected to a surface alkalinization treatment, and the interface of the mineral powder-grade red mud-open-graded acidic aggregate is modified through an acid-base neutralization reaction to enhance the interface bonding force, and the adhesion rate of the modified mixed aggregate to the grouting material reaches more than 85%;
[0034] S6. Then, the fiber solution and SBS modified asphalt were added in proportion, and stirred evenly at a temperature of 180±5°C using a mixer to prepare a red mud modified open-graded anti-cracking asphalt mixture;
[0035] S7. Finally, the red mud-based anti-cracking grouting material is poured into the red mud-modified open-graded anti-cracking asphalt mixture by self-leveling until the grouting is full. The red mud-based three-dimensional anti-cracking poured composite pavement mixture can be prepared by natural curing for 3 hours.
[0036] The beneficial effects of the present invention include:
[0037] 1. The red mud-based three-dimensional anti-cracking poured composite pavement mixture of the present invention has good anti-cracking performance. Multi-dimensional anti-cracking performance optimization is achieved by enhancing the self-cracking resistance of the grouting material, the fiber anti-cracking of the open-graded asphalt mixture, and the anti-cracking improvement after the interface performance is improved.
[0038] 2. The acidic aggregates used are widely sourced, which can reduce excessive dependence on aggregate resources in specific areas and reduce material procurement and transportation costs. At the same time, they can absorb a large amount of red mud, which can reduce the demand for traditional building materials such as natural mineral powder and cement, help protect the natural resources environment, reduce carbon emissions, and meet the current national strategic goals of sustainable development.
[0039] 3. Good economy, simple preparation process, and wide application range. It can extend the service life of the road surface, reduce the cost of road maintenance, and improve the return on investment.
[0040] Instruction Manual
[0041] Figure 1 The present invention is a flow chart for preparing a red mud-based three-dimensional anti-cracking pourable composite pavement mixture. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not limit the present invention.
[0043] Example 1
[0044] A red mud-based three-dimensional anti-cracking poured-in composite pavement mixture comprises the following components in parts by mass: 20 parts of red mud-based anti-cracking grouting material, including 9 parts of untreated red mud, 3 parts of calcium powder, 1 part of activator, 2 parts of water-reducing component, 2 parts of fiber and 2 parts of added water; 65 parts of red mud-modified open-graded anti-cracking asphalt mixture, including 15 parts of mineral powder-grade red mud, 45 parts of open-graded acidic aggregate, 3 parts of SBS modified asphalt and 2 parts of fiber.
[0045] In the red mud-based anti-cracking grouting material, the fineness of the untreated red mud is 0.075mm, the pass rate is 93%, and the water content is 26wt%; the calcium carbonate content of the calcium powder is 96.4wt%, the fineness reaches 400 mesh, and the water content is 0.32wt%; the activator is water glass; the water-reducing component is naphthalenesulfonate formaldehyde condensate; the fiber is basalt fiber, with a length of 12mm and a fineness of 10tex; the added water is ordinary tap water.
[0046] In the red mud modified open-graded anti-cracking asphalt mixture, the coarse aggregate material of the open-graded acidic aggregate is granite, the key sieve hole of the open-graded acidic aggregate is 4.75mm, the pass rate is 12%, and the target connected porosity is 22%; the particle size of the mineral powder grade red mud is less than 0.075mm, and the pH value is 7; the fiber is basalt fiber, with a length of 12mm and a fineness of 10tex.
[0047] Preparation process:
[0048] ①First, test the fineness and water content of the untreated red mud.
[0049] ② Place 4 parts of basalt fiber and 4 parts of added water into the container of an ultrasonic disperser and perform ultrasonic dispersion at a frequency of 40 kHz for 5 minutes to prepare a uniformly dispersed fiber solution.
[0050] ③Put 9 parts of untreated red mud and 2 parts of fiber solution prepared in step ② into a blender and mix slowly for 2 minutes, then add 3 parts of calcium powder, 1 part of water glass and 2 parts of naphthalenesulfonate formaldehyde condensate, and stir rapidly for 3 minutes to prepare a red mud-based anti-cracking grouting material.
[0051] ④ Design the grading of 45 parts by mass of open-graded acidic aggregate, with a target connected porosity of 22%. Add 15 parts of mineral powder-grade red mud to fill the aggregate voids to improve the overall strength and stability.
[0052] ⑤ The mixed aggregate of the above-mentioned open-graded acidic aggregate and mineral powder-grade red mud is conveyed into a heating drum via a belt, activated at a high temperature of 700°C for 3 minutes, and then subjected to surface alkalinity treatment. The interface of mineral powder-grade red mud-open-graded acidic aggregate is modified through acid-base neutralization reaction to enhance the interfacial adhesion. After modification, the adhesion rate of the mixed aggregate to the grouting material reaches 88%.
[0053] ⑥ Then add 2 parts of the fiber solution prepared in step ② and 3 parts of SBS modified asphalt, and stir evenly at 175° C. using a mixer to prepare a red mud modified open-graded anti-cracking asphalt mixture.
[0054] ⑦Finally, the red mud-based anti-cracking grouting material is self-leveled and poured into the red mud-modified open-graded anti-cracking asphalt mixture until the grouting is full. After natural curing for 3 hours, the red mud-based three-dimensional anti-cracking poured composite pavement mixture can be produced.
[0055] Table 1 Open graded acid aggregate gradation
[0056]
[0057] The performance tests of red mud-based anti-cracking grouting material, red mud-modified open-graded anti-cracking asphalt mixture and red mud-based three-dimensional anti-cracking poured composite pavement mixture are shown in Table 2, Table 3 and Table 4 respectively.
[0058] Table 2 Performance of red mud-based anti-cracking grouting materials
[0059] Detection indicators Test results 3d compressive strength / MPa 20.1 3d flexural strength / MPa 6.5 Initial fluidity / mm 165 30-minute fluidity / mm 160
[0060] Table 3 Performance of red mud modified open-graded anti-cracking asphalt mixture
[0061] Detection indicators Test results Porosity / % 23 Marshall stability / kN 7.1 Flow value / mm 3.2 Los Angeles wear value / % 11.4
[0062] Table 4 Performance of red mud-based three-dimensional anti-cracking poured composite pavement mixture
[0063] Detection indicators Test results Filling degree / % 93.3 Rutting dynamic stability times / mm 12240 Flexural strength / MPa 6.7 Bending stiffness modulus / MPa 2358
[0064] Example 2
[0065] A red mud-based three-dimensional anti-cracking poured-in composite pavement mixture comprises the following components in parts by mass: 25 parts of red mud-based anti-cracking grouting material, including 11 parts of untreated red mud, 3.5 parts of calcium powder, 2 parts of activator, 1 part of water-reducing component, 2.5 parts of fiber and 2.5 parts of added water; 73 parts of red mud-modified open-graded anti-cracking asphalt mixture, including 19 parts of mineral powder-grade red mud, 47 parts of open-graded acidic aggregate, 4.5 parts of SBS modified asphalt and 2.5 parts of fiber.
[0066] In the red mud-based anti-cracking grouting material, the fineness of the untreated red mud is 0.075mm, the pass rate is 95wt%, and the water content is 28wt%; the calcium carbonate content of the calcium powder is 97.2wt%, the fineness reaches 400 mesh, and the water content is 0.21wt%; the activator is water glass, and the water-reducing component is aliphatic hydroxysulfonate condensate; the fiber is polyethylene fiber, with a length of 16mm and a fineness of 9tex; the added water is ordinary tap water.
[0067] In the red mud modified open-graded anti-cracking asphalt mixture, the coarse aggregate material of the open-graded acidic aggregate is diorite, the key sieve hole 4.75mm pass rate of the open-graded acidic aggregate is 15%, and the target connected porosity is 25%; the particle size of the mineral powder grade red mud is less than 0.075mm, and the pH value is 8; the fiber is polyethylene fiber, with a length of 16mm and a fineness of 9tex.
[0068] Preparation process:
[0069] ①First, test the fineness and water content of the untreated red mud.
[0070] ② Place 5 parts of polyethylene fiber sample and 5 parts of added water into the container of an ultrasonic disperser and perform ultrasonic dispersion at a frequency of 50 kHz for 7 minutes to prepare a uniformly dispersed fiber solution.
[0071] ③ Put 11 parts of untreated red mud and 2.5 parts of fiber solution prepared in step ② into a blender and slowly mix and stir for 2.5 minutes, then add 3.5 parts of calcium powder, 2 parts of water glass and 1 part of aliphatic hydroxy sulfonate condensate, and stir rapidly for 4 minutes to prepare a red mud-based anti-cracking grouting material.
[0072] ④ Design the grading of 47 parts by mass of open-graded acidic aggregate, with a target connected porosity of 25%. Add 19 parts of mineral powder-grade red mud to fill the aggregate voids to improve the overall strength and stability.
[0073] ⑤ The mixed aggregate of the above-mentioned open-graded acidic aggregate and mineral powder-grade red mud is conveyed into a heating drum through a belt, activated at a high temperature of 800°C for 4 minutes, and then subjected to surface alkalinity treatment. The interface of mineral powder-grade red mud-open-graded acidic aggregate is modified through acid-base neutralization reaction to enhance the interfacial adhesion. After modification, the adhesion rate of the mixed aggregate to the grouting material reaches 90%.
[0074] ⑥ Then add 2.5 parts of the fiber solution prepared in step ② and 4.5 parts of SBS modified asphalt, and stir evenly at 180° C. using a mixer to prepare a red mud modified open-graded anti-cracking asphalt mixture.
[0075] ⑦Finally, the red mud-based anti-cracking grouting material is self-leveled and poured into the red mud-modified open-graded anti-cracking asphalt mixture until the grouting is full. After natural curing for 3 hours, the red mud-based three-dimensional anti-cracking poured composite pavement mixture can be produced.
[0076] Table 5 Open-graded acid aggregate mix proportions
[0077]
[0078] The performance tests of red mud-based anti-cracking grouting material, red mud-modified open-graded anti-cracking asphalt mixture and red mud-based three-dimensional anti-cracking poured composite pavement mixture are shown in Table 6, Table 7 and Table 8 respectively.
[0079] Table 6 Performance of red mud-based anti-cracking grouting material
[0080]
[0081]
[0082] Table 7 Performance of red mud modified open-graded anti-cracking asphalt mixture
[0083] Detection indicators Test results Porosity / % 24.6 Marshall stability / kN 8.4 Flow value / mm 2.8 Los Angeles wear value / % 9.5
[0084] Table 8 Red mud-based three-dimensional anti-cracking type poured composite pavement mixture properties
[0085] Detection indicators Test results Filling degree / % 96.3 Rutting dynamic stability times / mm 13264 Flexural strength / MPa 7.4 Bending stiffness modulus / MPa 2635
[0086] Example 3
[0087] A red mud-based three-dimensional anti-cracking poured-in composite pavement mixture comprises the following components in parts by mass: 35 parts of red mud-based anti-cracking grouting material, including 15 parts of untreated red mud, 4 parts of calcium powder, 3 parts of activator, 3 parts of water-reducing component, 3 parts of fiber and 3 parts of added water; 80 parts of red mud-modified open-graded anti-cracking asphalt mixture, including 20 parts of mineral powder-grade red mud, 50 parts of open-graded acidic aggregate, 6 parts of SBS modified asphalt and 4 parts of fiber.
[0088] In the red mud-based anti-cracking grouting material, the fineness of the untreated red mud is 0.075mm, the pass rate is 97%, and the water content is 29wt%; the calcium carbonate content of the calcium powder is 98.1wt%, the fineness reaches 400 mesh, and the water content is 0.1wt%; the activator is caustic soda, and the water-reducing component is naphthalenesulfonate formaldehyde condensate; the fiber is polypropylene fiber, with a length of 20mm and a fineness of 9tex; the added water is ordinary tap water.
[0089] In the red mud modified open-graded anti-cracking asphalt mixture, the coarse aggregate material of the open-graded acidic aggregate is tuff, the key sieve hole of the open-graded acidic aggregate is 4.75mm, the pass rate is 18%, and the target connected porosity is 28%; the particle size of the mineral powder grade red mud is less than 0.075mm, and the pH value is 9; the fiber is polypropylene fiber, with a length of 20mm and a fineness of 9tex.
[0090] Preparation process:
[0091] ①First, test the fineness and water content of the untreated red mud.
[0092] ② Place 7 parts of polypropylene fibers and 7 parts of added water into the container of an ultrasonic disperser and perform ultrasonic dispersion at a frequency of 60 kHz for 10 minutes to prepare a uniformly dispersed fiber solution.
[0093] ③ Put 15 parts of untreated red mud and 3 parts of fiber solution prepared in step ② into a blender and mix slowly for 3 minutes, then add 4 parts of calcium powder, 3 parts of caustic soda and 3 parts of naphthalenesulfonate formaldehyde condensate, and stir rapidly for 5 minutes to prepare a red mud-based anti-cracking grouting material.
[0094] ④ Design the grading of 50 parts by mass of open-graded acidic aggregate, with a target connected porosity of 28%. Add 20 parts of mineral powder-grade red mud to fill the aggregate voids to improve the overall strength and stability.
[0095] ⑤ The mixed aggregate of the above-mentioned open-graded acidic aggregate and mineral powder-grade red mud is conveyed into a heating drum through a belt, activated at a high temperature of 900°C for 5 minutes, and then subjected to surface alkalinity treatment. The interface of mineral powder-grade red mud-open-graded acidic aggregate is modified through acid-base neutralization reaction to enhance the interfacial adhesion. After modification, the adhesion rate of the mixed aggregate to the grouting material reaches 94%.
[0096] ⑥ Then add 4 parts of the fiber solution prepared in step ② and 6 parts of SBS modified asphalt, and stir evenly at 185° C. using a mixer to prepare a red mud modified open-graded anti-cracking asphalt mixture.
[0097] ⑦Finally, the red mud-based anti-cracking grouting material is self-leveled and poured into the red mud-modified open-graded anti-cracking asphalt mixture until the grouting is full. After natural curing for 3 hours, the red mud-based three-dimensional anti-cracking poured composite pavement mixture can be produced.
[0098] Table 9 Open-graded acid aggregate mix proportions
[0099]
[0100] The performance tests of red mud-based anti-cracking grouting material, red mud-modified open-graded anti-cracking asphalt mixture and red mud-based three-dimensional anti-cracking poured composite pavement mixture are shown in Table 10, Table 11 and Table 12 respectively.
[0101] Table 10 Performance of red mud-based anti-cracking grouting material
[0102] Detection indicators Test results 3d compressive strength / MPa 23.8 3d flexural strength / MPa 6.9 Initial fluidity / mm 174 30-minute fluidity / mm 170
[0103] Table 11 Performance of red mud modified open-graded anti-cracking asphalt mixture
[0104]
[0105]
[0106] Table 12 Performance of red mud-based three-dimensional anti-cracking poured composite pavement mixture
[0107] Detection indicators Test results Filling degree / % 97.4 Rutting dynamic stability times / mm 13657 Flexural strength / MPa 6.8 Bending stiffness modulus / MPa 2508
[0108] It can be found that the red mud-based three-dimensional crack-resistant poured composite pavement mixture has good performance, outstanding crack resistance, rutting dynamic stability greater than 12000 times / mm, flexural tensile strength greater than 6.5MPa, and bending stiffness modulus greater than 2300MPa; in addition, the red mud-based three-dimensional crack-resistant poured composite pavement mixture of the present invention can consume a large amount of industrial solid waste material red mud, while effectively solving the problem of pavement crack diseases, providing new ideas for the development of new road materials.
[0109] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A red mud-based three-dimensional anti-cracking pourable composite pavement mixture, characterized in that: The composition includes the following components in parts by weight: Red mud-based anti-cracking grouting material: 20-35 parts; Red mud modified open-graded anti-cracking asphalt mixture: 65-80 parts.
2. The red mud-based three-dimensional anti-cracking poured composite pavement mixture according to claim 1, characterized in that: The red mud-based anti-cracking grouting material comprises the following components in parts by mass: 9-15 parts of untreated red mud; 3-4 parts of calcium powder; 1-3 parts of stimulant; 1-3 parts of water reducing component; Fiber 2-3 servings; The added water and the fiber have the same mass fraction.
3. The red mud-based three-dimensional anti-cracking poured composite pavement mixture according to claim 2, characterized in that: In the red mud-based anti-cracking grouting material, the fineness of the untreated red mud meets the 0.075mm pass rate of more than 90%, and the water content is more than 25wt%; the calcium carbonate content of the calcium powder is more than 95wt%, the fineness is 400 mesh and above, and the water content is less than 0.5wt%.
4. The red mud-based three-dimensional anti-cracking poured composite pavement mixture according to claim 2, characterized in that: In the red mud-based anti-cracking grouting material, the activator is one of water glass and caustic soda; the water-reducing component is one of naphthalenesulfonate formaldehyde condensate and aliphatic hydroxysulfonate condensate; and the added water is ordinary tap water.
5. The red mud-based three-dimensional anti-cracking pourable composite pavement mixture according to claim 2, characterized in that: In the red mud-based anti-cracking grouting material, the fiber is at least one of basalt fiber, polyethylene fiber and polypropylene fiber, the fiber length ranges between 12 mm and 20 mm, and the fineness is less than 15 tex.
6. The red mud-based three-dimensional crack-resistant pouring composite pavement mixture according to claim 1, characterized in that: The red mud modified open-graded anti-cracking asphalt mixture comprises the following components in parts by weight: 15-20 parts of mineral powder grade red mud; 45-50 parts of open-graded acid aggregate; SBS modified asphalt 3-6 parts; Fiber 2-4 servings.
7. The red mud-based three-dimensional anti-cracking poured composite pavement mixture according to claim 6, characterized in that: In the red mud modified open-graded anti-cracking asphalt mixture, the coarse aggregate material of the open-graded acidic aggregate is granite, diorite or tuff, the key sieve hole 4.75mm pass rate is 12%-18%, and the target connected porosity is 22%-28%.
8. The red mud-based three-dimensional anti-cracking pourable composite pavement mixture according to claim 6, characterized in that: In the red mud modified open-graded anti-cracking asphalt mixture, the particle size of the mineral powder grade red mud is less than 0.075mm, and the pH value is 7-9, which is used to adjust the pH value of the open-graded acidic aggregate, perform interface modification on the open-graded acidic aggregate, and enhance the bonding force between the interfaces.
9. The red mud-based three-dimensional anti-cracking pourable composite pavement mixture according to claim 6, characterized in that: In the red mud modified open-graded anti-cracking asphalt mixture, the fiber is at least one of basalt fiber, polyethylene fiber and polypropylene fiber, the fiber length ranges between 12mm and 20mm, and the fineness is less than 15tex.
10. The method for preparing the red mud-based three-dimensional crack-resistant pouring composite pavement mixture according to claims 1-9, characterized in that: The following steps are involved: S1. Firstly, the fineness and water content of the untreated red mud are detected; S2. The fiber and the added water were placed in a container of an ultrasonic disperser and ultrasonically dispersed at a frequency of 40-60kHZ for 5-10min to prepare a uniformly dispersed fiber solution; S3. The untreated red mud and fiber solution were placed in a mixer and slowly mixed for 2-3 min, then calcium powder, activator and water-reducing component were added in proportion, and rapidly stirred for 3-5 min to form red mud-based anti-cracking grouting material; S4. Design the gradation of open-graded acidic aggregates, with a target connected porosity of 22%-28%, and add mineral powder-grade red mud in proportion to fill the aggregate voids to improve overall strength and stability; S5. The mixed aggregate of the open-graded acidic aggregate and the mineral powder-grade red mud is conveyed into a heating drum through a belt, activated at a high temperature of 700°C-900°C for 3-5 minutes, and then subjected to a surface alkalinization treatment, and the interface of the mineral powder-grade red mud-open-graded acidic aggregate is modified through an acid-base neutralization reaction to enhance the interface bonding force, and the adhesion rate of the modified mixed aggregate to the grouting material reaches more than 85%; S6. Then, the fiber solution and SBS modified asphalt were added in proportion, and stirred evenly at a temperature of 180±5°C using a mixer to prepare a red mud modified open-graded anti-cracking asphalt mixture; S7. Finally, the red mud-based anti-cracking grouting material is poured into the red mud-modified open-graded anti-cracking asphalt mixture by self-leveling until the grouting is full. The red mud-based three-dimensional anti-cracking poured composite pavement mixture can be prepared by natural curing for 3 hours.